1946
DOI: 10.1001/archotol.1946.00680050387005
|View full text |Cite
|
Sign up to set email alerts
|

OTITIS MEDIA: A Comparative Study of the Results Obtained in Therapy Before and After the Introduction of the Sulfonamide Compounds

Abstract: IN AN attempt to evaluate the effects of sulfonamide compounds used in the treatment of otitis media, the records of all patients with this disease admitted to the Los Angeles County General Hospital during the fiscal years of 1935 and 1943 were reviewed.Only those cases of otitis media in which the ear had drained for three days or longer were accepted in this series. This period of drainage was considered to establish with certainty the diagnosis of true purulent otitis media. SERIES (BEFORE THERAPEUTIC USE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…Up to this point no uniformly accepted diagnostic and therapeutic criteria have been established. Concerning its management, simple mastoidectomy has historically represented the standard surgical treatment of acute mastoiditis [2]. However, currently the rates of use of simple mastoidectomy in treating pediatric AM show considerable variations among reported series [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Up to this point no uniformly accepted diagnostic and therapeutic criteria have been established. Concerning its management, simple mastoidectomy has historically represented the standard surgical treatment of acute mastoiditis [2]. However, currently the rates of use of simple mastoidectomy in treating pediatric AM show considerable variations among reported series [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In the preantibiotic era, between 2% and 6% of patients with AM developed suppurative intracranial complications (ICCs), with fatal outcomes in 75% of them 3. Since the introduction of antibiotics, the incidence of AM has declined 4, 5. In 1959, Palva et al reported that 0.4% of their patients with acute otitis media (AOM) developed AM,6 whereas the reported incidence during the 1980s was 0.004% 7.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 6% of patients with acute or chronic suppurative otitis media developed intracranial complications, and mortality was greater than 80% 1, 2. With the introduction of sulfonamides, there was a 50% reduction in hospitalization for acute otitis media and an 80% reduction in mastoidectomies in children 3. The advent of widespread modern antibiotic use in the 1960s to 1980s resulted in a dramatic decrease in the incidence of these complications 4.…”
Section: Introductionmentioning
confidence: 99%